(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
Practical lessons are essential for the student’s learning process. However, teachers face numerous difficulties that prevent these classes from taking place, such as lack of essential materials due to the high cost of products, or even lack of teacher knowledge to perform practices. As teacher training is one of the most important missions of an educational institution and extension activities are one of the three pillars of the university, in order to minimize the obstacles described above, a training course was offered to school teachers, entitled "Microbiological Techniques Using Alternative Low-cost Conditions for Teaching Practices”. During the training course, two lectures were presented: Fundamentals of Microbiology and Biosafety in a Microbiology Laboratory Four practical workshops were also performed: 1 - Comparison of the efficiency of the pressure cooker, stove oven and autoclave in sterilization; 2 - Development of alternative culture media from agro-industrial residues; 3 - Evaluation of the efficiency of alternative culture media in the growth of bacteria and yeasts; 4 - Evaluation of the efficiency of alternative culture media in alcoholic fermentation by Saccharomyces cerevisiae; 5 - Microculture. Workshops were carried out using a variety of alternative materials in order to enable the future replication of these practices in schools. It is possible to suggest greater effectiveness in the teaching-learning process through teacher training to apply a differentiated methodological approach. Within this context, practical activities in the teaching of microbiology can be advantageous for the acquisition of knowledge by students of basic education.